Demographic movements in Slovene emigration to Argentina - Horvat, Avgust (Dve domovini, 1996)
A large majority of Slovene post-war political refugees left the displaced persons camps in Austria and Italy for Argentina, which was least discriminating in the accepting the immigrants. An organised immigrant community was quickly formed and Slovene families were established. As time passes there are more and more mixed marriages, the birth rate within the community is falling and the death rate increasing. Interest in working in the Slovene community has been falling and hence the future of this community is not at all certain.
Keywords: demografski razvoj; mortaliteta; nataliteta; Slovenci; Slovenes; slovenski izseljenci